2017
DOI: 10.18870/hlrc.v7i2.383
|View full text |Cite
|
Sign up to set email alerts
|

Making Sense of an Elusive Concept: Academics’ Perspectives of Quality in Higher Education

Abstract: Objective: Since the 1990s studies on how stakeholders in higher education perceive quality have burgeoned. Nevertheless, the majority of studies on perception of quality in higher education focus on students and employers. The few studies on academics’ perceptions of quality in higher education treat academics as a homogeneous group and, therefore, do not point out cross-disciplinary perspectives in perceptions of quality. This article explores how academics across six disciplines perceive quality in higher e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…So, whereas, external coercive pressures impose stakeholder expectations some of which may be unrealistic [39], HEIs are busy building internal quality assurance systems, improving education and training as well as developing future leaders internally [61]. Amidst institutional logics, most HEIs tend to initiate and open regional and internal research collaborations for knowledge acquisition, application and continuous improvement [42,13]. On the other hand, the efficacy of the institutional theoretical provisions can be seen in the external support advanced to HEIs in form of financing and regulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…So, whereas, external coercive pressures impose stakeholder expectations some of which may be unrealistic [39], HEIs are busy building internal quality assurance systems, improving education and training as well as developing future leaders internally [61]. Amidst institutional logics, most HEIs tend to initiate and open regional and internal research collaborations for knowledge acquisition, application and continuous improvement [42,13]. On the other hand, the efficacy of the institutional theoretical provisions can be seen in the external support advanced to HEIs in form of financing and regulation.…”
Section: Discussionmentioning
confidence: 99%
“…There is no agreed position as to what constitutes quality in higher education [11]. However, quality as a relative concept [33] has been defined as a standard of excellence [12] aimed at fitness for purpose and transformation [13]. In HEIs, quality could mean a standard upon which the core mandate of HEIs such as teaching, research and community engagements are judged.…”
Section: Internal Quality Assurance In Higher Education Institutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nabaho et al posited that for youth to be self-employed, they should acquire basic skills through entrepreneurship education. They emphasized that the possession of these skills will consolidate and enhance their businesses as well as eliminate early failure [14]. From the data collated and analyzed, it was found that, psychomotor skills have the ability to focus on tasks to be accomplished, manipulative skills have ability to produce and accomplish task in their business and ability to determine new ways of manipulating things.…”
Section: Research Findingsmentioning
confidence: 99%
“…Qualitative data such as opinions, views, perceptions, suggestions and explanations were analysed thematically by creating categories of themes, summarizations and synthesising. Different scholars such as Mugenta and Mugenda (2003), Kombo and Tromp (2006) and Gall, Gall, and Borg (2007) are in favour of this view. Quantitative data was presented through tables and qualitative data through paraphrasing, explanations and quotations.…”
Section: Approaches To Improving Participation Rate In Courses Evaluamentioning
confidence: 99%